Observation of the electromagnetic field effect via charge-dependent directed flow in heavy-ion collisions at the relativistic heavy ion collider - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review. X, Expanding access, 2024)
The deconfined quark-gluon plasma (QGP) created in relativistic heavy-ion collisions enables the exploration of the fundamental properties of matter under extreme conditions. Noncentral collisions can produce strong magnetic fields on the order of 1018  G, which offers a probe into the electrical conductivity of the QGP. In particular, quarks and antiquarks carry opposite charges and receive contrary electromagnetic forces that alter their momenta. This phenomenon can be manifested in the collective motion of final-state particles, specifically in the rapidity-odd directed flow, denoted as 𝑣1⁡(𝗒). Here, we present the charge-dependent measurements of 𝑑⁢𝑣1/𝑑⁢𝗒 near midrapidities for 𝜋±, 𝐾±, and 𝑝⁡(p[bar]) in Au+Au and isobar (9644Ru+9644Ru and 9640Zr+9640Zr) collisions at √𝑠NN=200  GeV, and in Au+Au collisions at 27 GeV, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The combined dependence of the 𝑣1 signal on collision system, particle species, and collision centrality can be qualitatively and semiquantitatively understood as several effects on constituent quarks. While the results in central events can be explained by the 𝑢 and 𝑑 quarks transported from initial-state nuclei, those in peripheral events reveal the impacts of the electromagnetic field on the QGP. Our data put valuable constraints on the electrical conductivity of the QGP in theoretical calculations.
*STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 350 weitere Personen]